Evaluation of effectiveness of Blue-Green Infrastructure for reduction of pluvial flooding under climate change and internal system failure conditions - Mugume, Seith N.; Nakyanzi, Lydia Patricia (IWA Publishers, 2024)
Blue-Green Infrastructure (BGI) has been proposed as a suitable adaptation measure that can enhance the resilience of existing urban drainage systems (UDSs). However, there are limited studies that have rigorously investigated the performance of BGI options considering future climate change and internal UDS failures. In this study, a coupled 1D–2D PCSWMM model was developed and applied to investigate the effectiveness of potential BGI options in the reduction of pluvial flooding using a case study of a ‘failed’ UDS in Kampala, Uganda. The study results suggest that climate change will increase the frequency of occurrence of extreme rainfall from 1 in 100 years to 1 in 10 years, thereby exacerbating the urban flooding challenge in Kampala City. The study results also ascertained that the use of spatially distributed infiltration trenches and bioretention cells at a catchment scale could lead to a modest reduction of the total flood volume and the average flood duration of at least 12.0% [9.8–14.0%] and 34.3%, respectively, when combined with improved UDS cleaning and maintenance. The findings point towards the need to implement BGI options in combination with improved asset management and investments in the expansion of grey UDSs to enhance global resilience to pluvial flooding under climate change.